2017
DOI: 10.1016/j.hrthm.2016.12.026
|View full text |Cite
|
Sign up to set email alerts
|

Role of protein kinase C in metabolic regulation of the cardiac Na+ channel

Abstract: Background NADH increases in cardiomyopathy, activates protein kinase C (PKC), upregulates mitochondrial reactive oxygen species (mitoROS), and downregulates the cardiac Na+ channel (Nav1.5). Objective The objective was to determine how NADH signals downregulation of Nav1.5. Methods Isolated mouse cardiomyocytes were used for patch clamp recording and to monitor mitoROS with MitoSOX™ Red. HEK293 cells were used for transient transfections. HEK293 cells stably expressing human Nav1.5 were utilized for singl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
43
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 39 publications
0
43
1
Order By: Relevance
“…Other studies, however, have demonstrated that NADH-mediated PKC phosphorylation at S1503 modulates single channel conductance (58). In addition to NADH directly activating PKC by increasing phospholipase D activity and diacylglycerol levels, NAD ϩ has been shown to increase Na v 1.5 activity through PKA-mediated phosphorylation (57,58). Interestingly, in hearts isolated from mice that are haploinsufficient for Na v 1.5, perfusion of NAD ϩ for 20 min was protective against arrhythmogenesis assessed by programmed electrical stimulation.…”
Section: Biosynthesis and Metabolism Of Nad ϩmentioning
confidence: 89%
See 1 more Smart Citation
“…Other studies, however, have demonstrated that NADH-mediated PKC phosphorylation at S1503 modulates single channel conductance (58). In addition to NADH directly activating PKC by increasing phospholipase D activity and diacylglycerol levels, NAD ϩ has been shown to increase Na v 1.5 activity through PKA-mediated phosphorylation (57,58). Interestingly, in hearts isolated from mice that are haploinsufficient for Na v 1.5, perfusion of NAD ϩ for 20 min was protective against arrhythmogenesis assessed by programmed electrical stimulation.…”
Section: Biosynthesis and Metabolism Of Nad ϩmentioning
confidence: 89%
“…PKC, in turn, phosphorylates Na v 1.5 at S1503 to decrease channel surface expression (98). Other studies, however, have demonstrated that NADH-mediated PKC phosphorylation at S1503 modulates single channel conductance (58). In addition to NADH directly activating PKC by increasing phospholipase D activity and diacylglycerol levels, NAD ϩ has been shown to increase Na v 1.5 activity through PKA-mediated phosphorylation (57,58).…”
Section: Biosynthesis and Metabolism Of Nad ϩmentioning
confidence: 99%
“…Recently a metabolic pathway for PKC activation has been described where the elevated levels of NADH activate PKCδ, resulting in a decrease in I Na . Interestingly, this decrease in I Na was not because of any change in surface expression but rather channel conductance was decreased directly by phosphorylation of serine 1503 in Na V 1.5 channels and indirectly by increasing ROS production in mitochondria .…”
Section: Modulation Of Kinetics and Trafficking Of Nav15 Channel By mentioning
confidence: 99%
“…Recently a metabolic pathway for PKC activation has been described where the elevated levels of NADH activate PKCδ, resulting in a decrease in I Na . Interestingly, this decrease in I Na was not because of any change in surface expression but rather channel conductance was decreased directly by phosphorylation of serine 1503 in Na V 1.5 channels and indirectly by increasing ROS production in mitochondria . The PKCδ antagonism completely reversed both decrease in I Na and ROS production from the mitochondria while specific inhibition of PKCα could partially recover I Na without any effect on ROS production, thus indicating the involvement of more than one PKC isozyme.…”
Section: Modulation Of Kinetics and Trafficking Of Nav15 Channel By mentioning
confidence: 99%
See 1 more Smart Citation